Pengaruh Kualitas Pelayanan dan Persepsi Nilai Terhadap Loyalitas Nasabah Pengguna Kartu ATM pada Bank Sumsel Babel Syariah KCP UIN Raden Fatah Palembang Melalui Kepuasan Nasabah Sebagai Variabel Intervening - Nirma Fitriana; Hilda Hilda; Riduwansah Riduwansah (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2024)
This research aims to determine the influence of service quality and perceived value on customer loyalty of ATM card users at BSB Syariah KCP UIN Raden Fatah Palembang through satisfaction as an intervening variable. This research uses primary data with a quantitative approach in the form of distributing questionnaires with a sample collection method using purposive sampling with the Hair et.al formula which received as many as 150 respondents. The research instrument testing technique uses SEM-PLS using an analysis tool in the form of SmartPLS version 3.0. The results of this research show that: (1) service quality has a positive and significant effect on customer loyalty; (2) perceived value has a positive and significant effect on customer loyalty; (3) service quality has a positive and significant effect on customer satisfaction; (4) perceived value has a positive and significant effect on customer satisfaction; (5) customer satisfaction has a positive and significant effect on customer loyalty; (6) service quality has a positive and significant effect on customer loyalty through customer satisfaction as an intervening variable; (7) perceived value has a positive and significant effect on customer loyalty through customer satisfaction as an intervening variable.